2015
DOI: 10.1364/oe.23.011183
|View full text |Cite
|
Sign up to set email alerts
|

Broadband nonlinear optical response in multi-layer black phosphorus: an emerging infrared and mid-infrared optical material

Abstract: Black phosphorous (BP), the most thermodynamically stable allotrope of phosphorus, is a high-mobility layered semiconductor with direct band-gap determined by the number of layers from 0.3 eV (bulk) to 2.0 eV (single layer). Therefore, BP is considered as a natural candidate for broadband optical applications, particularly in the infrared (IR) and mid-IR part of the spectrum. The strong light-matter interaction, narrow direct band-gap, and wide range of tunable optical response make BP as a promising nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
350
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 658 publications
(372 citation statements)
references
References 46 publications
12
350
3
Order By: Relevance
“…We further performed a comparison experiment on pure NMP solution, which was verifi ed to be absent of nonlinear saturable absorption effect. [ 38 ] These results confi rm that the saturable absorption response indeed originates from the intrinsic optical absorption in BPQDs other than NMP solution. BP possesses bandgap from 0.3 to 1.5 eV with thickness of BP from bulk degrading to monolayer.…”
Section: Nonlinear Optical Absorption Properties Of Bpqdssupporting
confidence: 58%
See 1 more Smart Citation
“…We further performed a comparison experiment on pure NMP solution, which was verifi ed to be absent of nonlinear saturable absorption effect. [ 38 ] These results confi rm that the saturable absorption response indeed originates from the intrinsic optical absorption in BPQDs other than NMP solution. BP possesses bandgap from 0.3 to 1.5 eV with thickness of BP from bulk degrading to monolayer.…”
Section: Nonlinear Optical Absorption Properties Of Bpqdssupporting
confidence: 58%
“…[28][29][30][31] Mechanical and liquid exfoliation methods have been adopted to prepare BP nanosheets with different numbers of layers and sizes. [32][33][34] Due to thickness-dependent bandgap structure of BP which is tunable ranged from 0.3 eV (bulk) to 1.5 eV (monolayer) [ 26,35,36 ] and anomalous anisotropy, [ 37 ] BP nanosheets show nonlinear saturable absorption properties, [ 38 ] and used as the saturable absorber for fi ber lasers. [ 39,40 ] However, the lateral size and thickness of these BP nanosheets is hardly to be controlled by the liquid exfoliation methods, which limits the investigations of the nonlinear optical properties of the BP with special size.…”
mentioning
confidence: 99%
“…It was also reported that BP powder was obtained by grinding bulk BP crystal dispersed in different solvents such as IPA, NMP and ethyl alcohol (EA) to obtain 1 mg mL –1 dispersions, and the dispersions were ultrasonicated for 2 h. The dispersions were then allowed to settle for more than 24 h to enable the removal of large‐size sedimentations by centrifugation (at 1500 rpm for 20 min) 12. The interesting fact behind the formation of thin BP nanoflakes in the solution is that the interlayer van der Waals bonding is broken down by the ultrasonic energy 95…”
Section: Fabrication Of Few‐layered Bpmentioning
confidence: 99%
“…The NMP solvent for obtaining stable, highly concentrated (≈0.4 mg mL –1 ) BP dispersions was used in LPE in most of the reported studies 12, 67, 85, 91, 95, 118, 160, 166, 183, 185, 186, 187. NMP and DMF are well suit for liquid exfoliation owing to their relatively high boiling points and surface tension (≈40 mJ m –2 ) 166, 183, 188.…”
Section: Fabrication Of Few‐layered Bpmentioning
confidence: 99%
“…To obtain ultrashort pulses, the laser generally require a saturable absorber to achieve the mode locking mechanism. Various approaches have been developed since the early days of ultrafast lasers including physical light intensity absorbers such as semiconductor saturable absorption mirrors (SESAMs) [6], [7], carbon nanotubes [8], [9], graphene [10], [11], topological insulators [12], [13], black phosphorous [14], [15], and most recently transition-metal dichalcogenides (TMDs) [16], [17]. However, these physical absorbers either have bandwidth limitation or stability issues.…”
Section: Introductionmentioning
confidence: 99%